Digital Preservation. - Deegan, Marilyn (Digital futures., 2013)
Digital preservation is an issue of huge importance to the library and information profession. It is a complex issue involving many different aspects and views. This book uses case studies and examples to ground the ideas and theories in real concerns and practice. It covers key issues in digital preservation; web archiving; strategies; and more.